ANALISIS PENERAPAN PEMBELAJARAN DIFERENSIASI GURU TERHADAP KETERCAPAIAN PEMBELAJARAN PENDIDIKAN JASMANI DI SDN PASIRPANJANG - Irawan, Dicky Aditya; Susilawati, Dewi; Muhtar, Tatang (JURNAL ILMU KEOLAHRAGAAN, 2024)
This study aims to see how teachers apply differentiated learning models in PE lessons in elementary schools, precisely at SDN Pasirpanjang to find solutions to these problems and determine the achievement of differentiated learning in this study using qualitative research with descriptive methods using data collection techniques carried out in triangulation (observation, interviews, questionnaires and documentation). qualitative research where qualitative research is more based on the philosophy of postpositivism / interpretive. Data analysis is inductive / qualitative and the results of the research In the results of this study researchers sought data by observing the activities of sports teachers in class VI SD Negeri Pasirpanjang Kab. Bandung in the learning process. Based on Observation Interviews and Questionnaires regarding the learning process carried out can be said to be good. This research is intended to see and evaluate previous research that this differentiation learning is very suitable to be applied in physical education learning at the elementary school level, and is effective in teaching and learning activities between educators and students. With the results that can be shown in this study, students are very good at responding to the differentiated learning approach model because it hones their interests and talents. Based on the results of this study it can be concluded that. The application of differentiated learning models in physical education lessons is very helpful The application of differentiated learning models in physical education lessons is very helpful to achieve the results of physical education learning objectives in elementary schools. By helping students become more active creative and innovative, so that students can learn independently to build positive character for students